Clinical significance of preoperative renal function and gross hematuria for intravesical recurrence after radical nephroureterectomy for upper tract urothelial carcinoma. (22nd November 2016) - Hashimoto, Takeshi; Nakashima, Jun; Kashima, Takeshi; Hirasawa, Yosuke; Shimodaira, Kenji; Gondo, Tatsuo; Nakagami, Yoshihiro; Namiki, Kazunori; Horiguchi, Yutaka; Ohno, Yoshio; Ohori, Makoto; Tachibana, Masaaki
Abstract : Objectives: To investigate the predictive values of perioperative factors and to develop a nomogram for intravesical recurrence after radical nephroureterectomy in patients with upper urinary tract urothelial carcinoma. Methods: A retrospective analysis of 144 patients who underwent radical nephroureterectomy from 1996 to 2014 was carried out. The actuarial probabilities of the intravesical recurrence‐free survival rate were calculated using the Kaplan–Meier method. Prognostic indicators for intravesical recurrence were identified using competing‐risks regression analyses. Results: Intravesical recurrence occurred in 63 patients during the follow‐up period. The intravesical recurrence‐free survival rates at 1, 3, and 5 years were 65.7%, 50.6% and 47.1%, respectively. In univariate analysis, the presence of gross hematuria ( P = 0.028) and the preoperative serum creatinine level ( P = 0.033) were significantly associated with intravesical recurrence. In multivariate analysis, the presence of gross hematuria (subdistribution hazard ratio 2.03, 95% CI 1.145–3.496; P = 0.013) and the preoperative serum creatinine level (subdistribution hazard ratio 3.15, 95% CI 1.161–3.534; P = 0.021) were independent predictors for intravesical recurrence after radical nephroureterectomy. Accordingly, a nomogram based on the model was developed. The concordance index of this model was 0.632. Conclusion: The presence of gross hematuria and preoperative serum creatinine levels seem to be independent predictors for intravesical recurrence after radical nephroureterectomy. Our nomogram developed based on these factors might aid in appropriate patient selection for clinical trials of novel therapeutic interventions, including administration of intravesical chemotherapy.